Distribution and Diversity of Freshwater Crabs (Decapoda: Brachyura: Potamidae, Gecarcinucidae) in Iranian Inland Waters - Farhadi, Ardavan; Harlioglu, Muzaffer Mustafa (Istanbul Univ Press, Fac Aquatic Sciences, 2018)
This article reviews the current knowledge of primary freshwater crabs (Decapoda, Brachyura) in Iranian inland waters, with the purpose of classifying the exact number of species, the threat status, and their distribution and diversity. Previous studies have reported that Iranian inland waters have eight freshwater crab species and there was no accurate information on the distribution of freshwater crab species in Iran. This review article describes that an additional six freshwater crab species, Potamon gedrosianum, P. magnum, P. mesopotamicum, P. ilam, Sodhiana blanfordi, and S. iranica, are also present in Iran. Therefore, there are 14 freshwater crab species currently known in Iran, which belong to two families (Gecarcinucidae and Potamidae). The genus Potamon is represented by 11 species, and the genus Sodhiana is represented by 3 species (found in south and south east of Iran). In addition, this review presents a distribution map and the possible threats for each species.
Keywords: Brachyura; decapoda; freshwater crabs; distribution; Iran